Cyclic AMP efflux, via MRPs and A1 adenosine receptors, is critical for bovine sperm capacitation - Osycka Salut, Claudia Elena (2014)
Sperm capacitation has been largely associated with an increase in cAMP, although its relevance in the underlying mechanisms of this maturation process remains elusive. Increasing evidence shows that the extrusion of cAMP through multidrug resistance associated protein 4 (MRP4) regulates cell homeostasis not only in physiological but also in pathophysiological situations and studies from our laboratory strongly support this assumption. In the present work we sought to establish the role of cAMP efflux in the regulation of sperm capacitation. Sperm capacitation was performed in vitro by exposing bovine spermatozoa to bicarbonate 40 and 70 mM; cAMP; probenecid (a MRPs general inhibitor) and an adenosine type 1 receptor (A1 adenosine receptor) selective antagonist (DPCPX). Capacitation was assessed by chlortetracycline assay and lysophosphatidylcholine-induced acrosome reaction assessed by PSA-FITC staining. Intracellular and extracellular cAMP was measured by radiobinding the regulatory subunit of PKA under the same experimental conditions. MRP4 was detected by western blot and immunohistochemistry assays. Results showed that the inhibition of soluble adenylyl cyclase significantly inhibited bicarbonate-induced sperm capacitation. Furthermore, in the presence of 40 and 70 mM bicarbonate bovine spermatozoa synthesized and extruded cAMP. Interestingly, in the absence of IBMX (a PDEs inhibitor) cAMP efflux still operated in sperm cells, suggesting that cAMP extrusion would be a physiological process in the spermatozoa complementary to the action of PDE. Blockade of MRPs by probenecid abolished the efflux of the cyclic nucleotide resulting not only in the accumulation of intracellular cAMP but also in the inhibition of bicarbonate-induced sperm capacitation. The effect of probenecid was abolished by exposing sperm cells to cAMP. The high-affinity efflux pump for cAMP, MRP4 was expressed in bovine spermatozoa and localized to the midpiece of the tail as previously reported for soluble adenylyl cyclase and A1 adenosine receptor. Additionally, blockade of A1 adenosine receptor abolished not only bicarbonate-induced sperm capacitation but also that stimulated by cAMP. Present findings strongly support that cAMP efflux, presumably through MRP4, and the activation of A1 adenosine receptor regulate some events associated with bicarbonate-induced sperm capacitation, and further suggest a paracrine and/or autocrine role for cAMP.